Establishment of the optimal harvest time of botanical seeds of Espeletia grandiflora for the propagation and conservation of the species (Research, Society and Development, 2023)
In order to contribute to the conservation of frailejones by facilitating their dynamic propagation, the best time to harvest seeds of E. grandiflora was determined. The morphological description of the inflorescence and achenes was carried out, taking into account the number and weight of full, empty and total seeds per inflorescence (weight of 1000 seeds), establishing the percentage of full and empty seeds and the percentage of germination per inflorescence. Additionally, the tetrazolium test was carried out (four replicates of 100 seeds per treatment). It was found that the number of total seeds decreased significantly with a higher phenological stage of formation and maturity of the inflorescence, reporting values of 68.64, 59 and 47.56 respectively at stages 1, 2 and 3. Likewise, analysing the variable weight of 1000 full seeds, it was found that the highest values were presented when harvesting inflorescences with bracts and peduncles without brown hairs (stage 3). For the germination percentage, the highest values were found in the seeds at stage 2, apparently influenced by extrinsic factors that limited the germination process in the seeds of stage 3 and intrinsic factors for stage 1. Finally, the viability analysis showed the highest results for phenological stage 3, with 70% viability; however, there was no significant difference with respect to phenological stage 2, which showed 68%, but there was a significant difference with respect to stage 1.